Factors influencing return to sports after anterior cruciate ligament reconstruction - Maryam Zaighum; Sumaiya Khan; Kazim Najjad; Muhammad Sufyan; Dhanesh Khatri; Muhammad Anwar; Gharira Batool; Komal Saleem (Khyber Medical University Journal)
Objectives:  to assess the frequency of return to sports (RTS) after anterior cruciate ligament reconstruction (ACLR) and to identify factors influencing RTS in individuals from Karachi, Pakistan.